Phase control of quasi-2D perovskite thin films by adding MAPbI3 in the precursor solution. Issue 36 (30th August 2022) - Wang, Meng; You, Jiayu; Xu, Cunyun; Dong, Jun; Luo, Chuanyao; Song, Qunliang; Zhang, Sam
Abstract : With proper 3D MAPbI3 addition, the content and distribution of different phases is regulated. A a relative balance between the photovoltaic performance and stability of quasi-2D perovskite cells is achieved. Abstract : Quasi two-dimensional (Q-2D) perovskite cells have attracted much attention due to their excellent stability compared to their 3D counterparts. However, the Q-2D perovskite thin films prepared by the solution method have been confirmed to be a mixture of small- n phases and large- n phases instead of a pure phase, where the amount and distribution of these phases have a great significance on the performance of Q-2D perovskite solar cells. Here, commercialized 3D perovskite powder was simply added to an ACI perovskite precursor solution to get a uniform and closely connected heterostructure in which the large- n phases can work as pathways for charge transfer. The characterization results of the films and devices show that the appropriate amount of MAPbI3 in the precursor solution could distribute the 3D phases homogeneously within the final film to promote the photovoltaic performance of the devices. Consequently, the power conversion efficiency of the Q-2D ACI perovskite solar cell has been increased from 10.4% to 13.82% (with a 32.8% performance improvement).